Detection of cfxA2, cfxA3, and cfxA6 genes in beta-lactamase producing oral anaerobes - Buhle BINTA; Mrudula PATEL (University of São Paulo, 2016)
ABSTRACT Purpose The aim of this study was to identify β-lactamase-producing oral anaerobic bacteria and screen them for the presence of cfxA and BlaTEM genes that are responsible for β-lactamase production and resistance to β-lactam antibiotics. Material and Methods Periodontal pocket debris samples were collected from 48 patients with chronic periodontitis and anaerobically cultured on blood agar plates with and without β-lactam antibiotics. Presumptive β-lactamase-producing isolates were evaluated for definite β-lactamase production using the nitrocefin slide method and identified using the API Rapid 32A system. Antimicrobial susceptibility was performed using disc diffusion and microbroth dilution tests as described by CLSI Methods. Isolates were screened for the presence of the β-lactamase-TEM (BlaTEM) and β-lactamase-cfxA genes using Polymerase Chain Reaction (PCR). Amplified PCR products were sequenced and the cfxA gene was characterized using Genbank databases. Results Seventy five percent of patients carried two species of β-lactamase-producing anaerobic bacteria that comprised 9.4% of the total number of cultivable bacteria. Fifty one percent of β-lactamase-producing strains mainly Prevotella, Porphyromonas, and Bacteroides carried the cfxA gene, whereas none of them carried blaTEM. Further characterization of the cfxA gene showed that 76.7% of these strains carried the cfxA2 gene, 14% carried cfxA3, and 9.3% carried cfxA6. The cfxA6 gene was present in three Prevotella spp. and in one Porphyromonas spp. Strains containing cfxA genes (56%) were resistant to the β-lactam antibiotics. Conclusion This study indicates that there is a high prevalence of the cfxA gene in β-lactamase-producing anaerobic oral bacteria, which may lead to drug resistance and treatment failure.